Noninvasive endoscopic hemostasis technique for post‐papillectomy bleeding using a novel self‐assembling peptide (with video). Issue 1 (25th December 2022) - Miyano, Akira; Ogura, Takeshi; Nishikawa, Hiroki
Abstract: Although a novel hemostatic agent has been used for endoscopic mucosal resection in submucosal dissection, there are few case reports of its use in pancreato‐biliary endoscopic procedures. We describe a case of post‐endoscopic papillectomy bleeding in which endoscopic hemostasis was achieved using a novel hemostatic agent. Abstract : Although a novel hemostatic agent has been used for endoscopic mucosal resection in submucosal dissection, there are few case reports of its use in pancreato‐biliary endoscopic procedures. We describe a case of post‐endoscopic papillectomy bleeding in which endoscopic hemostasis was achieved using a novel hemostatic agent.